Combination treatment of disseminated granuloma annulare - Arfenya E. Karamova; Lyudmila F. Znamenskaya; Svetlana I. Svishchenko; Mar'yana B. Zhilova; Maria A. Nefedova; Anna S. Pugner (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
Purpose. To present the results of the treatment of disseminated form of granuloma annulare with remote long-wave ultraviolet therapy and low level laser therapy. Material and methods. Two female patients at the age of 50 and 53 years with complaints of generalised eruptions on the skin of the trunk, upper and lower limbs and a histologically confirmed diagnosis were treated using a combination of remote long-wave ultraviolet therapy and low level laser therapy of infrared spectrum. 16 sessions of remote long-wave ultraviolet therapy and 10 sessions of low level laser therapy were conducted directly on the lesions. Considering the multidirectionality of the mechanisms of action of phototherapy and laser therapy, the procedures were carried out on different days or with many hours long intervals. Results. Combined use of the remote long-wave ultraviolet therapy and laser therapy led to a significant improvement by the 21st day of the treatment. No side effects were noticed during the treatment, tolerance of the sessions was good. Conclusion. Combined use of the remote long-wave ultraviolet therapy and low level laser therapy of infrared spectrum is effective in treatment of disseminated form of granuloma annulare.